2017
DOI: 10.3389/fnins.2017.00186
|View full text |Cite
|
Sign up to set email alerts
|

Compression at Myofascial Trigger Point on Chronic Neck Pain Provides Pain Relief through the Prefrontal Cortex and Autonomic Nervous System: A Pilot Study

Abstract: Compression at myofascial trigger points (MTrPs), known as “ischemic compression,” has been reported to provide immediate relief of musculoskeletal pain and reduce the sympathetic activity that exacerbates chronic pain. We conducted a pilot study to investigate the possible involvement of the prefrontal cortex in pain relief obtained by MTrP compression in the present study, and analyzed the relationships among prefrontal hemodynamic activity, activity of the autonomic nervous system, and subjective pain in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 89 publications
(105 reference statements)
2
36
0
1
Order By: Relevance
“… Education regarding nutrition variables that impact the ANS ( Buchhorn, Hauk, Meint, & Willaschek, 2016 ; Dippacher, Willaschek, & Buchhorn, 2014 ; Kitamura, Torii, Uneyama, & Niijima, 2010 ; Kopp, 2009 ; Luyer, Habes, van Hak, & Buurman, 2011 ). Graded exercise programs ( Gagnon, Galli, Friedman, Grilli, & Iverson, 2009 ; J. Leddy et al, 2016 ; Sanudo, Carrasco, de Hoyo, Figueroa, & Saxton, 2015 ; C. O. Tan, Meehan, Iverson, & Taylor, 2014 ) Relaxation and meditation protocols in their various forms ( Charalambous, Giannakopoulou, Bozas, & Paikousis, 2015 ; Jerath, Edry, Barnes, & Jerath, 2006 ; Pal, Velkumary, & Madanmohan, 2004 ; Tang, Holzel, & Posner, 2015 ) Positive event scheduling ( Kop et al, 2011 ; McCraty, Atkinson, Tiller, Rein, & Watkins, 1995 ) Treatment of cervical strain, mobility, and pain issues ( Marshall, Vernon, Leddy, & Baldwin, 2015 ; Morikawa et al, 2017 ; Morin et al, 2016 ; Ye, Lee, Lin, & Chuang, 2017 ) …”
Section: Ans Informed Concussion Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… Education regarding nutrition variables that impact the ANS ( Buchhorn, Hauk, Meint, & Willaschek, 2016 ; Dippacher, Willaschek, & Buchhorn, 2014 ; Kitamura, Torii, Uneyama, & Niijima, 2010 ; Kopp, 2009 ; Luyer, Habes, van Hak, & Buurman, 2011 ). Graded exercise programs ( Gagnon, Galli, Friedman, Grilli, & Iverson, 2009 ; J. Leddy et al, 2016 ; Sanudo, Carrasco, de Hoyo, Figueroa, & Saxton, 2015 ; C. O. Tan, Meehan, Iverson, & Taylor, 2014 ) Relaxation and meditation protocols in their various forms ( Charalambous, Giannakopoulou, Bozas, & Paikousis, 2015 ; Jerath, Edry, Barnes, & Jerath, 2006 ; Pal, Velkumary, & Madanmohan, 2004 ; Tang, Holzel, & Posner, 2015 ) Positive event scheduling ( Kop et al, 2011 ; McCraty, Atkinson, Tiller, Rein, & Watkins, 1995 ) Treatment of cervical strain, mobility, and pain issues ( Marshall, Vernon, Leddy, & Baldwin, 2015 ; Morikawa et al, 2017 ; Morin et al, 2016 ; Ye, Lee, Lin, & Chuang, 2017 ) …”
Section: Ans Informed Concussion Treatmentmentioning
confidence: 99%
“…Treatment of cervical strain, mobility, and pain issues ( Marshall, Vernon, Leddy, & Baldwin, 2015 ; Morikawa et al, 2017 ; Morin et al, 2016 ; Ye, Lee, Lin, & Chuang, 2017 )…”
Section: Ans Informed Concussion Treatmentmentioning
confidence: 99%
“…Pain pressure threshold revealed significant time-by-group interaction(p,.001):Pain pressure threshold increase in patients who had TrP dry needling as compared to those who had TrP manual therapy (between group difference: post treatment, 59.0 kPa; 95% CI: 40.0,69.2; 1-week follow-up,69.2kPa;95% CI: 49.5,79.1; 2-week follow-up, 78.9kPa; 95% CI:49.5,89.0).it was concluded that pain, disability and cervical range of motion share similar outcome measures in 2 session treatment. Those in the TrP DN group experienced greater improvement in PPT over cervical spine [40].…”
Section: Literature Reviewmentioning
confidence: 89%
“…According to [101], a reduction of cervical chronic pain is associated with a reduction of the LF component of HRV, an increase of the HF component and a reduction of the LF/HF ratio.…”
Section: Pain Of Musculoskeletal Origin and Hrvmentioning
confidence: 99%